Color, texture and flavor development of maraschino style papaya - Villanueva, Emerita Peckson 1940- (1961)
Maraschino style papaya was prepared to simulate Maraschino cherries for color, texture and flavor qualities. The products as compared to Marashino cherries were evaluated by 10 judges. Results of color stability tests show erythrosins dye applied by Cruss' methods A an B to be stable after one month storage. The other dyes used all faded after this period. No condition for lime treatment is found to result in a texture that is similar with that of cherries although the products tested resulted in a satisfactory and acceptable texture. Likewise, the amount of flavoring that simulated the flavor of cherries has not been determined although adding 28 drops of almond extract is fairly precise in simulating the cherry taste.